2019
DOI: 10.3758/s13421-019-00925-5
|View full text |Cite
|
Sign up to set email alerts
|

A context-change account of temporal distinctiveness

Abstract: The distinctiveness effect refers to the finding that items that stand out from other items in a learning set are more likely to be remembered later. Traditionally, distinctiveness has been defined based on item features; specifically, an item is deemed to be distinctive if its features are different from the features of other to-be-learned items. We propose that distinctiveness can be redefined based on context change-distinctive items are those with features that deviate from the others in the current tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 81 publications
1
16
0
1
Order By: Relevance
“…We allowed for two distinct drift values, , the standard drift (implemented for low-RPE events), and d , a β higher level of drift for high-RPE events. This approach (i.e., increased drift in response to high-RPE events) is in line with how contextual disruptions due to salient changes have been previously modeled (Horner et al, 2016;Polyn et al, 2009;Siefke et al, 2019). We moreover use d for the first item presented to the network as a way of capturing classic primacy effects in memory (i.e., the higher probability of retrieving the first item in a sequence; see 7.5 for further discussion of how primacy is modeled here, compared to how it is usually modeled in CMR).…”
Section: Updating Temporal Context and Associative Matrices During Resupporting
confidence: 73%
See 1 more Smart Citation
“…We allowed for two distinct drift values, , the standard drift (implemented for low-RPE events), and d , a β higher level of drift for high-RPE events. This approach (i.e., increased drift in response to high-RPE events) is in line with how contextual disruptions due to salient changes have been previously modeled (Horner et al, 2016;Polyn et al, 2009;Siefke et al, 2019). We moreover use d for the first item presented to the network as a way of capturing classic primacy effects in memory (i.e., the higher probability of retrieving the first item in a sequence; see 7.5 for further discussion of how primacy is modeled here, compared to how it is usually modeled in CMR).…”
Section: Updating Temporal Context and Associative Matrices During Resupporting
confidence: 73%
“…In our paradigm, these two factors (RPE and shift-in-latent-cause) were confounded --in future work, we can try to unconfound them (e.g, by having isolated high-reward or low-reward items that do not indicate a lasting change in the underlying mean reward value). Related to this point, Siefke et al (2019) recently ran a study that attempted to unconfound context change and prediction error, using stimuli that varied in their background color; results from that study supported the hypothesis that context change, not prediction error per se , is the key determinant of discontinuities in mental context. More work is needed to see if this applies to our RPE paradigm.…”
Section: High Rpes Form Event Boundaries In Memorymentioning
confidence: 92%
“…Likewise, item pairs are also remembered as having occurred farther apart in time if they spanned an event boundary compared to items that had been encountered in the same context 1,4,18 . Event boundaries can also influence nontemporal aspects of episodic memory, such as enhancing associative memory for an item and any co-incident contextual information (e.g., background color 16,20 ). The existing literature therefore presents a complex story, whereby temporal aspects of episodic memory integration are disrupted by changes in the surrounding context, while other elements of the new context present at event boundaries are enhanced in memory.…”
mentioning
confidence: 99%
“…In contrast, when the task is markedly item-focused, the Distinctiveness Approach trumps the Shared Context Approach 8 . This was the case in a recent study 41 , which found that distinctiveness enhances item's source memory of color. These diverging findings emphasize the importance of task demands in determining the reliance on shared context or temporal distinctiveness in supporting sequence memory.…”
Section: Discussionmentioning
confidence: 81%